Understanding the Drivers of Islamic Credit Card Selection Using TRA Model: Evidence from Khyber Pakhtunkhwa, Pakistan - Khan, Khush Dil; Khan, Ikram Ullah; Khan, Safeer Ullah (iRASD Journal of Economics, 2022)
This study investigates the drivers of Islamic Credit Card (ICC) adoption in Khyber Pakhtunkhwa (KP), Pakistan by using the extended Theory of Reasoned Action (TRA) model. Particularly, the study examines the impact of subjective norms, attitude, perceived financial cost, knowledge, and social influence on ICC selection. Using a convenient sampling technique, this study relied on self-administered questionnaires that were distributed among Islamic banks’ customers in Kohat and Bannu divisions. A total of 400 questionnaires were distributed, and 340 valid questionnaires were selected for the final analysis. The results from the regression analysis indicate that the factors i.e., subjective norm, customer attitudes, knowledge, and social influence have a positive and significant effect on the intentions to use the ICC, but perceived financial cost shows a negative effect on the intentions to use ICC. Among the predictors, the subjective norm was found a very influential driver to forecast the intention to use ICC. Our results provide insights to managers of Islamic banks, policymakers, and Sariah scholars to understand how to promote ICC.